Perspektif Hukum Laut Internasional: Illegal Fishing Di Kepulauan Natuna - Sadrak A. F. Ambanaga; Agussalim Burhanuddin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Illegal fishing is a pressing issue in Indonesia, particularly in the Natuna Islands, where China's controversial nine-dash line claim has exacerbated the problem. This research focuses on the international law of the sea to address illegal fishing in the Natuna region. The research uses a qualitative method, which explores the legal framework in regulating illegal fishing. The findings highlight the legal challenges Indonesia faces in combating illegal fishing in the Natuna Islands, emphasizing the disruptive impact on marine ecosystems and national sovereignty. The research concludes that international law, particularly the 1982 UNCLOS, defines Indonesia's maritime boundaries, the 2001 IPOA on IUU Fishing classifies illegal fishing, and the 1995 Code of Conduct for Responsible Fisheries regulates fisheries management. In addition, the report also suggests that Indonesia request Particularly Sensitive Sea Area status from the International Maritime Organization for the Natuna Islands waters.